2023
DOI: 10.3174/ajnr.a7865
|View full text |Cite
|
Sign up to set email alerts
|

A Pragmatic Randomized Trial Comparing Surgical Clipping and Endovascular Treatment of Unruptured Intracranial Aneurysms

Abstract: BACKGROUND AND PURPOSE: Surgical clipping and endovascular treatment are commonly used in patients with unruptured intracranial aneurysms. We compared the safety and efficacy of the 2 treatments in a randomized trial. MATERIALS AND METHODS:Clipping or endovascular treatments were randomly allocated to patients with one or more 3-to 25-mm unruptured intracranial aneurysms judged treatable both ways by participating physicians. The study hypothesized that clipping would decrease the incidence of treatment failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…By contrast, the rate of residual saccular aneurysms in the endovascularly treated group was 15%. 19 Furthermore, some studies suggest that clipping may be a more cost-effective method of treatment. [20][21][22] In addition, we confirmed several known patient-specific and aneurysm-specific risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, the rate of residual saccular aneurysms in the endovascularly treated group was 15%. 19 Furthermore, some studies suggest that clipping may be a more cost-effective method of treatment. [20][21][22] In addition, we confirmed several known patient-specific and aneurysm-specific risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the aneurysms treated in our database was comparable with large prospective randomized trials on ruptured and unruptured aneurysms and considered representative. 19,28 In general, reports on complication rates vary in the literature. However, the rates in our study are comparable with those in large meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
“…22 Most studies reporting the morbidity and mortality of surgical clipping are single-center retrospective reviews. Most recently, Darsaut et al 29 performed a pragmatic randomized trial comparing UIA clipping ligation to endovascular treatment in 7 centers over 10 years. Morbidity and mortality (modified Rankin Scale score >2) at 1 year occurred in 3/143 and 3/148 (2% [95% CI, 1%–6%]) patients allocated to surgery and endovascular treatments, respectively.…”
Section: Surgical Treatment Modalitiesmentioning
confidence: 99%
“…22 Most studies reporting the morbidity and mortality of surgical clipping are single-center retrospective reviews. Most recently, Darsaut et al 29 30 In 2019, Algra et al's systemic review and meta-analysis of 114 studies reported a complication risk of 4.9% and a case-fatality risk of 0.3%. 31 However, microsurgical techniques have evolved over the years, with improvement in microsurgical instruments, intraoperative diagnostic tools (catheter angiography, indocyanine-green, Doppler, ultrasound, and flow cytometry), and avoidance of fixed brain retractors causing cerebral contusions.…”
Section: Surgical Treatment Modalities Microsurgerymentioning
confidence: 99%
“…Both ISAT 4 and BRAT 5 1-year outcomes demonstrated improved clinical outcomes for patients who underwent ruptured aneurysm coiling compared with clipping, but these randomized controlled trials (RCTs) are becoming outdated (especially with regards to EVT) and also included all aneurysms, so that the results are not directly applicable to WNAs. More recently, the CURES trial 6 compared EVT and clipping for unruptured aneurysms and found better angiographic outcomes (primary outcome) with clipping with similar final clinical outcomes (secondary outcomes). There were, however, more new neurological deficits and longer hospitalizations with clipping.…”
Section: Justin R Mascitellimentioning
confidence: 99%